The Scientific Imaginary in Visual Culture - Smelik, Anneke (2010)
Popular media, art and science are intricately interlinked in contemporary visual culture. This book analyses the ›scientific imaginary‹ that is the result of the profound effects of science upon the imagination, and conversely, of the imagination in and upon science. As scientific developments in genetics, information technology and cybernetics open up new possibilities of intervention in human lives, cultural theorists have explored the notion of the ›posthuman‹. The Scientific Imaginary in Visual Culture analyses figurations of the ›posthuman‹ in history and philosophy, as well as in its utopian and dystopian forms in art and popular culture. The authors thus address the blurring boundaries between art and science in diverse media like science fiction film, futurist art, video art and the new phenomenon of ›bio-art‹. In their evaluations of the scientific imaginary in visual culture, the authors engage critically with current scientific and technological concerns.